Síntese e caracterização de sais benzimidazolínios como ligantes fluorescentes de quadruplex-G - Volpato, William Gomes (2025)
This study presents the synthesis and characterization of benzimidazolinium halides as fluorescent ligands for guanine structures found in RNA and DNA, known as G-quadruplexes. The methodology for obtaining the compounds was carried out in three steps, starting from 2- aryl-1H-benzo[d]imidazole (1) via 5-exo-tet cyclization, followed by its alkylation with ethyl bromide to form 2-aryl-1-ethyl-1H-benzo[d]imidazole (2), which then reacts with alkyl halides to form benzimidazolinium salts (3 and 4). The reaction conditions for obtaining 3-alkyl-2-aryl1-ethyl-1H-benzo[d]imidazolinium halides (3a–3f, 4a) were optimized, resulting in seven examples with yields of up to 76%. The structural characterization of the compounds was performed using 1H and 13C NMR, ESI-MS mass spectrometry, and HRMS. The thermal stability of the compounds was investigated by TGA, which demonstrated an increase in thermal stability for the charged compound series 3 and 4 compared to the neutral compounds in series 2. Additionally, compounds containing electron-withdrawing groups exhibited greater thermal stability, as observed in the 5% weight loss temperatures, 3e (245 °C) ~ 3d (247 °C). Photophysical characterization showed absorption and emission near 280 nm and 360 nm, respectively, with a higher fluorescence quantum yield in protic polar solvents. The elucidation of the photophysical properties of compounds 3 and 4 through semi-empirical TD-DFT calculations indicated π→π* and n→π* transitions, further explaining the hypsochromic shift observed in solution. Intermolecular interactions were investigated via saturation transfer STDNMR between compound 3d and the G4 precursor, 5'-disodium guanosine monophosphate, indicating greater proximity between the hydrogen atoms H-7 and H-4 of the compound and H-B of guanosine, suggesting affinity with the G4 precursor. The study highlights the innovation of employing this technique for validating potential G4 sensors. The compounds in this series demonstrated potential as G4 sensors in aqueous media, exhibiting good thermal stability and well-defined photophysical properties, with the possibility of application in optoelectronic devices.